Inhibitory actions of bisabolol on α7-nicotinic acetylcholine receptors - Nurulain, Syed M.; Petroianu, Georg (Neuroscience, 2015)
Bisabolol is a plant-derived monocyclic sesquiterpene alcohol with antinociceptive and antiinflammatory actions. However, molecular targets mediating these effects of bisabolol are poorly understood. In this study, using a two-electrode voltage-clamp and patch-clamp techniques and live cellular calcium imaging, we have investigated the effect of bisabolol on the function of human α7 subunit of nicotinic acetylcholine receptor (nAChR) in Xenopus oocytes, interneurons of rat hippocampal slices. We have found that bisabolol reversibly and concentration dependently (IC50=3.1μM) inhibits acetylcholine (ACh)-induced α7 receptor-mediated currents. The effect of bisabolol was not dependent on the membrane potential. Bisabolol inhibition was not changed by intracellular injection of the Ca2+ chelator BAPTA and perfusion with Ca2+-free solution containing Ba2+, suggesting that endogenous Ca2+-dependent Cl− channels are not involved in bisabolol actions. Increasing the concentrations of ACh did not reverse bisabolol inhibition. Furthermore, the specific binding of [125I] α-bungarotoxin was not attenuated by bisabolol. Choline-induced currents in CA1 interneurons of rat hippocampal slices were also inhibited with IC50 of 4.6μM. Collectively, our results suggest that bisabolol directly inhibits α7-nAChRs via a binding site on the receptor channel.
Gesehen am 08.01.2018
Available online 15 August 2015